TEACHER'S EFFORTS TO MOTIVATE STUDENTS TO THE IMPORTANCE OF ENGLISH THROUGH MANAGING ENGLISH LEARNING IN THE CLASS ( A Study at SMA N 5 Tidore Islands and SMA YASMU Sofifi ) - Djafar, Hariyanti; Tamhir, Lukman (British (Jurnal Bahasa dan Sastra Inggris), 2021)
This study aims to know how the students' motivation of learning English, how is the teacher's way to motivate students to learn English, and how the effect of learning management on students. The method use was descriptive qualitative. Data was collected by doing observation, interviews, documentation, and questions. The results of this study stated that students were motivated to learn English caused by two factors, which are an internal stimulus and external stimulus. A teacher should know first these two things before determining what appropriate method to apply. The good of teacher's learning management would help students learning English. Smart students should not always be allowed to work alone in group assignments. This method makes students with the type of external stimulus even more unmotivated. Keywords: Efforts, Motivation, Managing Class.